Criminal Act of Sexual Gratification: Fiqh JinÄyah and Positive Law Perspective - Nugraheni, Nadea Lathifah (Al-Ahkam, 2018)
This paper describes the concept of sexual gratification based on positive legal views in Indonesia and fiqh jinÄyah. This type of qualitative research with the method of collecting library data is also normative in looking at and approaching cases of sexual gratification. This study uses several approaches, including case, comparison, and conceptual approaches. The government has regulated the Law Number. 31 of 1999 which has been updated by Law Number. 20 of 2001 on combating corruption. Moreover, it is stated in Article 12 B that explains matters including gratuities, such as money, goods, commissions, checks, travel tickets and other public facilities. Basically, the sanction of sexual gratification has fulfilled government regulations but has not yet been applied. Thus, it is necessary to reform the law of sexual gratification in Indonesia. The theory of Mukhtalath in Islamic law can be an alternative solution to cases of sexual gratification. The synchronicity of the role of the government and the clear rules and regulations relating to cases of sexual gratuity are urgently needed to achieve justice and legal validity.[]Tulisan ini mendeskripsikan konsep gratifikasi seksual berdasarkan pandangan hukum positif di Indonesia dan fiqh jinÄyah. Penelitian ini berjenis kualitatif dengan metode pengumpulan data kepustakaan juga bersifat normatif dalam memandang dan melakukan pendekatan terhadap kasus gratifikasi seksual. Penelitian ini menggunakan beberapa pendekatan, diantaranya pendekatan kasus, perbandingan dan konseptual. Pemerintah telah mengatur UU Nomor. 31 Tahun 1999 yang telah diperbaharui oleh UU Nomor. 20 tahun 2001 tentang pemberantasan korupsi. Terlebih tercantum dalam pasal 12 B yang menjelaskan hal-hal yang termasuk gratifikasi, seperti, uang, barang, komisi, check, tiket perjalanan dan fasilitas umum lainya. Pada dasarnya sanksi gratifikasi seksual telah memenuhi aturan pemerintah, akan tetapi belum diaplikasikan. Dengan demikian perlu pembaharuan terhadap hukum gratifikasi seksual di Indonesia. Teori tentang Mukhtalath dalam hukum islam dapat menjadi alternatif solusi akan kasus gratifikasi seksual. sinkronisitas peran pemerintah dan jelasnya aturan perundang-undangan terkait kasus gratifikasi seksual sangat dibutuhkan demi tercapainya keadilan dan keabsahan hukum.